Carcinogenicity of High Consumption of Meat and Lung Cancer Risk Among Non-Smokers: A Comprehensive Meta-Analysis. (2nd January 2018) - Gnagnarella, Patrizia; Caini, Saverio; Maisonneuve, Patrick; Gandini, Sara
ABSTRACT: Increasing evidence suggests that high consumption of meat is linked to lung cancer but the previous meta-analyses did not properly address the role of tobacco smoking as a potential confounder. We conducted a meta-analysis to investigate the association of lung cancer, among never smokers, with consumption of various type of meat, fish, heterocyclic amines and polycyclic aromatic hydrocarbons. We performed a systematic literature search and meta-analysis, for highest versus lowest consumption and dose-response. The results from random effects models summarized data from 14 independent observational studies and 5368 lung cancer cases. We found a statistically significant 24% increased risk of lung cancer for high consumption of red meat (Summary Relative Risk 1.24, 95% CI 1.01–1.51), based on 11 estimates, with low heterogeneity (I 2 = 31%) and no indication of publication bias. No significant associations between high consumption of other types of meat, fish nor for heterocyclic amines and lung cancer risk were detected. No significant risk estimates were found for the increase of one serving per week of any type of meat or fish. Our meta-analysis suggests that a high intake of red meat may increases the risk of lung cancer among never and non-smokers.